2016
DOI: 10.1186/s13098-016-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of a real time continuous glucose monitoring system as an educational tool for patients with gestational diabetes

Abstract: BackgroundWomen with gestational diabetes mellitus (GDM) are required to control their blood glucose shortly after GDM diagnosis to minimize adverse pregnancy outcomes. A real time-continuous glucose monitoring system (RT-CGMS) provides the patient with continuous information about the alterations in levels of the blood glucose. This visibility may empower the patient to modify her lifestyle and engage in therapeutic management. The aim of this study was to determine whether a single application of RT-CGMS to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 14 publications
1
59
1
Order By: Relevance
“…The number of study participants with type 2 diabetes among existing studies (31,32) is small (total n = 56). Moreover, a number of small randomized controlled trials performed among GDM women have reported reduced gestational weight gain (33) and higher detection rates for those who required medication therapy (34) but have found no improvement in glycemic control or pregnancy outcomes with CGMS use (33,35). Conversely, a cohort study performed among 340 GDM women showed better pregnancy outcomes in the CGMS group (36).…”
Section: Clinical Use Of Cgms During Pregnancymentioning
confidence: 99%
“…The number of study participants with type 2 diabetes among existing studies (31,32) is small (total n = 56). Moreover, a number of small randomized controlled trials performed among GDM women have reported reduced gestational weight gain (33) and higher detection rates for those who required medication therapy (34) but have found no improvement in glycemic control or pregnancy outcomes with CGMS use (33,35). Conversely, a cohort study performed among 340 GDM women showed better pregnancy outcomes in the CGMS group (36).…”
Section: Clinical Use Of Cgms During Pregnancymentioning
confidence: 99%
“… 10 , 15–18 Reported barriers to CGM use include technical challenges, calibration, skin irritation, frequent alarms (especially during sleep), differences between sensor and SMBG measurements, and cost. 10 , 17 , 19 Despite the positive outcomes in the recent Continuous Glucose Monitoring in Pregnant Women with Type 1 Diabetes (CONCEPTT) study, more than 80% of the women experienced frustrations with CGM, such as connectivity issues, alarms, and calibration errors, and 48% of participants experienced skin reactions following sensor use. 20 With the limited evidence of improved clinical outcomes, combined with the lack of published accuracy data for continuous sensing during pregnancy and the high cost of such systems, use of continuous glucose sensing is generally underutilized in the pregnant population.…”
Section: Introductionmentioning
confidence: 99%
“…They used a similar real-time CGM for 3 to 7 days (mean of 67 hours). 18 They did not see a difference in glycemic control or perinatal outcomes.…”
Section: Resultsmentioning
confidence: 94%